Theoretical and experimental investigations on a compact TE11 mode bend for high‐power transmission line - Keqiang Wang; Hao Li; Tianming Li; Chaoxiong He (IET Microwaves, Antennas & Propagation, 2024)
Abstract The oversized TE11 mode bend is able to make the transmission direction of electromagnetic wave to turn 90°, and it is one of the key components in the high‐power microwave system. The mode coupling characteristics between the TE11 and parasitic modes under two different polarisations in the bending waveguide are analysed, and it is found that the TE11 suffers less interferences from parasitic modes when its polarisation direction is perpendicular to the bending plane, and the corresponding 90° TE11 bend is easier to realise high performance. To verify this analysis, an oversized 90° TE11 bend waveguide working at 10 GHz is designed, and its structural length is only 7.5 times the central working wavelength. Simulated results indicate that its relative bandwidth is 15.6% when the transmission efficiency is over 98%, and its maximum power handling capacity reaches 5.6 GW at short microwave pulse duration (less than 100 ns). The S‐parameters indicate that its S21 is about −0.1 dB from 9.5 to 10.5 GHz, and its S11 is under −25 dB in the same frequency range. Meanwhile, the high power test indicates that the bend works stably when the injected power is 3 GW.